Polycage membranes for precise molecular separation and catalysis - Xiang Li; Weibin Lin; Vivekanand Sharma; Radoslaw Gorecki; Munmun Ghosh; Basem A. Moosa; Sandra Aristizabal; Shanshan Hong; Niveen M. Khashab; Suzana P. Nunes (Nature Communications, 2023)
Abstract The evolution of the chemical and pharmaceutical industry requires effective and less energy-intensive separation technologies. Engineering smart materials at a large scale with tunable properties for molecular separation is a challenging step to materialize this goal. Herein, we report thin film composite membranes prepared by the interfacial polymerization of porous organic cages (POCs) (RCC3 and tren cages). Ultrathin crosslinked polycage selective layers (thickness as low as 9.5 nm) are obtained with high permeance and strict molecular sieving for nanofiltration. A dual function is achieved by combining molecular separation and catalysis. This is demonstrated by impregnating the cages with highly catalytically active Pd nanoclusters ( ~ 0.7 nm). While the membrane promotes a precise molecular separation, its catalytic activity enables surface self-cleaning, by reacting with any potentially adsorbed dye and recovering the original performance. This strategy opens opportunities for the development of other smart membranes combining different functions and well-tailored abilities.